2015
DOI: 10.1038/aps.2014.154
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin ameliorates ischemic neuronal damage in vitro via adenosine A1 receptor-mediated transactivation of epidermal growth factor receptor

Abstract: Aim: Paeoniflorin from Chinese herb Paeoniae Radix has been shown to ameliorate middle cerebral artery occlusion-induced ischemia in rats. The aim of this study was to investigate the mechanisms underlying the neuroprotective action of PF in cultured rat cortical neurons. Methods: Primary cultured cortical neurons of rats were subjected to oxygen-glucose deprivation and reoxygenation (OGD/R) insult. Cell survival was determined using MTT assay. HEK293 cells stably transfected with A 1 R (HEK293/A 1 R) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…There are a lot of major active constituents of P. lactiflora that have been identified, including paeoniflorin (PF), albiflorin (AF), oxypaeoniflorin, paeonilactinone, benzoyloxypaeoniflorin, and lactinolide [ 2 ]. It is well documented that PF possesses remarkable effects for pain [ 3 , 4 ], muscle spasm [ 5 , 6 ], inflammation [ 7 , 8 ], and neurodegenerative disorders [ 9 , 10 ]. However, few pharmacological studies of AF were reported.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of major active constituents of P. lactiflora that have been identified, including paeoniflorin (PF), albiflorin (AF), oxypaeoniflorin, paeonilactinone, benzoyloxypaeoniflorin, and lactinolide [ 2 ]. It is well documented that PF possesses remarkable effects for pain [ 3 , 4 ], muscle spasm [ 5 , 6 ], inflammation [ 7 , 8 ], and neurodegenerative disorders [ 9 , 10 ]. However, few pharmacological studies of AF were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of EGFR activity has been considered a potential therapeutic strategy to treat some cardiovascular diseases, including hypertension and cardiac hypertrophy (Forrester et al, ). However, according to several recent studies, EGFR also contributes to protective responses under some conditions, such as chronic isoproterenol stimulation and ischemic/infarction damage (Reichelt, O'Brien, Thomas, & Headrick, ), possibly through activating PI3K/AKT‐ and/or ERK‐dependent antioxidative pathway (Seo et al, ; Zhong, Song, Xu, Ye, & Feng, ). Here, we showed that AS‐III treatment induces TACE activation in bEnd.3 cells, which further causes EGFR transactivation and consequent activation of AKT and ERKs pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a variety of epilepsy models have been established, such as those induced by chemical agents and electrical stimulation. The epilepsy model induced by intraperitoneal injection of lithium chloride-pilocarpine has unique pathophysiological processes 13 . The changes in EEG of rats during seizures are similar to those in humans.…”
Section: Discussionmentioning
confidence: 99%